Global patterns of light saturation and photoinhibition of lake primary production. Issue 4 (1st January 2016) - Staehr, Peter A.; Brighenti, Ludmila S.; Honti, Mark; Christensen, Jesper; Rose, Kevin C.
Abstract: The effect of light availability on lake gross primary production (GPP) depends on the physical setting and meteorological and chemical conditions characterizing the lake. Although it has long been recognized that complex interactions between external and in-lake conditions affect whole-lake GPP, few studies have evaluated the importance of different drivers of daily and seasonal variability in GPP for a diverse set of lake types. In this study, we used a unique dataset covering a wide spectrum of lakes in terms of size, nutrient loading, and phytoplankton biomass, combined with high-frequency meteorology, dissolved oxygen (DO), and light data to determine the GPP of the lakes and to investigate the degree of light limitation and photoinhibition of GPP over multiple time scales. A Bayesian modeling approach was employed to model diel changes in DO as a nonlinear function of light and temperature, making it possible to determine the parameters describing the light dependency of hourly GPP rates under in situ conditions. Of the 900 days analyzed, 43% had moderate to strongly light-saturated GPP during midday summer conditions, and photoinhibition occurred on 77% of these days. GPP became increasingly light-limited with increasing nutrient and phytoplankton concentrations, conditions that also reduced the likelihood of photoinhibition. The highest summer rates of GPP were found in the light-limited, nonphotoinhibited lakes with elevated nutrient concentrations and phytoplankton biomass, although annual rates were much lower in these systems. Our results show that the interaction of light and nutrients affects the magnitude and temporal variability of GPP in lake ecosystems.